Analysis of discrimination towards the mental health of women COVID-19 survivors - Shamsiah Abd Kadir,; Faridah Dahalan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Infectious disease patients such as those with HIV, AIDS, TB and Leprosy have always been shunned by society. They often face discrimination such as people refusing casual contact and social isolation from the community due to the stigma people hold. These discriminatory actions have a detrimental effect on the patients’ emotional and mental health. The effect is reported to other infectious diseases such as COVID-19. Discrimination toward COVID-19 survivors was high in 2021. Despite the sentiments going down in 2022, no studies have been conducted to explore the phenomenon. Hence, this study attempts to understand the causes and effects on the mental health of women COVID-19 survivors. Therefore, the study employed qualitative research to determine the causes and effects on the mental health of women COVID-19 survivors. To arrive at the result, researchers interviewed six COVID-19 survivors that were infected in 2021 and 2022 purposely from civilian, media, and medical practitioners. The result of the study discovered four themes namely ‘Public Reaction Towards COVID-19 Survivors’, ‘Survivors’ Behaviour During the Mistreatment’, ‘Mental Health of Survivors facing Public Discrimination’, and ‘Causes of the Discrimination according to the Survivors’ - all of which answered the research question developed. By creating an indicator that recognises early warning systems of potential indicators of conflict, the government may be able to address this issue as well as other potential kinds of discrimination. Besides that, media practitioners must adhere to Peace Journalism elements and Society of Professional Journalists to promote social stability.